If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 5r + -7r Combine like terms: 5r + -7r = -2r 6 = -2r Solving 6 = -2r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '2r' to each side of the equation. 6 + 2r = -2r + 2r Combine like terms: -2r + 2r = 0 6 + 2r = 0 Add '-6' to each side of the equation. 6 + -6 + 2r = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 2r = 0 + -6 2r = 0 + -6 Combine like terms: 0 + -6 = -6 2r = -6 Divide each side by '2'. r = -3 Simplifying r = -3
| 16=4n | | 7x^2=30x-8 | | 12t^(2/5)+19t^(1/5)+4=0 | | x/7+45=-60 | | 4(y+5)-6y=2 | | x/7+45= | | 12b+2a=8 | | 3(8x-5)=24 | | 3/8x-1/12=x/3 | | a+5b=19 | | (5/3)(1/3)+1/3^3 | | 12a+2b=8 | | 2x+35=43 | | 15x-8=4x-19 | | 8n+n=9 | | m/-4-3=21 | | -15x(-8)= | | 6(w-6)-8w=-20 | | 4(5x-5)-12= | | 2(3x-1)=7x-3 | | 7+5v+8=-10 | | 5/3*1/3+1/3^3 | | 8n+5=-52+65n | | 4w-12=40 | | 9.2=5.7+h/6+0.6 | | 2/3(1/8+8x)-1/8=7/8 | | -71=64x | | x+4/6=-4 | | 4c=21-1c | | 12a+4r=4.6 | | 6(u+6)-3=21 | | 4v=88 |